Analysis and Evaluation of the Practice of Using Business Climate Transformation Tools in Russia - S. V. Muzalyov; V. V. Narbut; E. V. Nikiforova; O. V. Schneider (Учёт. Анализ. Аудит, 2025)
The article presents a comprehensive analysis of the transformation processes of the business climate in Russia, based on a study of the mechanisms of interaction between government institutions and the business community. The purpose of the study is to analyze the mechanisms of interaction between the state and business to improve the business climate in Russia. research methods include statistical analysis, surveys of entrepreneurs, assessment of investment activity and factors influencing business development. The article considers the urgent problem of forming an effective feedback system between government authorities and business as a key factor in the successful implementation of strategic transformations in the country’s economy. Based on extensive statistical material and the results of surveys of representatives of the business community, modern trends in the investment activity of Russian enterprises are studied. A detailed analysis of factors that have a significant impact on the business climate is carried out, including an assessment of lending conditions, availability of labor resources and the effectiveness of government support measures. The main barriers to the development of entrepreneurial activity are identified and systematized, among which special attention is paid to administrative restrictions, problems of access to financial resources and imperfections of legal regulation. The paper proposes an innovative approach to the formation of a comprehensive system for monitoring and evaluating the effectiveness of initiatives to improve the business climate. The need to create a multi-channel communication system between government institutions and business, including both traditional interaction formats and modern digital tools, is substantiated. Particular attention is paid to issues of ensuring transparency in the process of making management decisions and mechanisms for taking into account the opinion of the business community. The practical significance of the study lies in the development of specific recommendations for improving the mechanisms of interaction between the state and business, aimed at creating favorable conditions for the development of entrepreneurship, stimulating investment activity and increasing the competitiveness of the Russian economy in modern conditions.